Physicochemical and Sensory Quality of Probiotic Drink from Sumbawa Wild Horse Milk (Faculty of Animal Science Universitas Brawijaya, 2023)
Sumbawa wild horse milk is pure milk produced from Sumbawa horses with high nutritional content. It can survive for five months at room temperature without processing and has health benefits. However, the utilization of Sumbawa wild horse milk is still limited because of its low sensory quality due to natural fermentation, which also adversely affects its acceptability. Adding probiotic bacteria is one of the methods to improve its quality. This study aims to develop and analyze the physicochemical and sensory quality of probiotic drink products from Sumbawa wild horse milk by adding probiotic bacteria. This study used a one-factor, Completely Randomized Design (CRD), namely different types of starters. The treatment in this study is using probiotic starter Lactobacillus rhamnosus (P1) and commercial starter Lactobacillus bulgaricus + Streptococcus thermophilus (P2). The probiotic drink from Sumbawa wild horse milk in the treatment P1 has the best results, pH 4.35, 0.55% titratable acidity, 13.10% total dissolved solids, 78.00 mPa.s viscosity, 74.66% syneresis, and 3.42x109 CFU/ml total LAB. The most preferred product based on the hedonic test is P2. P2 has a whiter color and more sour taste. The addition of probiotic starters can improve the physicochemical product, and commercial starters can improve the sensory quality of the product.